Looking After Number Two? Competition, Cooperation and Workplace Interaction - Tim Barmby; John G. Sessions; Alexandros Zangelidis (Institute for the Study of Labor (IZA), 2013)
We build a model of worker interdependence in which two workers can either compete or cooperate and compare performance under either scenario to that of a single worker working in isolation. We show that whilst competition unequivocally reduces performance, cooperation may raise or lower performance. Employing a unique data set in which workgroups are comprised of either one or two workers, we are able to test explicitly for the presence of cooperation. We find empirical support for cooperative behavior.
Keywords: J33; J41; J54; 330; absence; worker interdependency